Mechanical properties of coconut shell powder reinforced PVC composites in automotive applications / Muhammad Hanafi Md Sah … [et al.] - Md Sah, Muhammad Hanafi; Mohd Noor, Alias; Abbas, Muhammad Rabiu; Abu Bakar, Aznizam (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Coconut shell powder (CSP) (which is used in reinforced Polyvinyl Chloride (PVC)) is one of the possible candidates of materials suitable as automotive components; however, appropriate tests need to be done to evaluate whether it meets all requirements. CSP-reinforced composites are made with PVC matrix within the range of 0 - 20 phr and the effect of the reinforcement of the natural fibres on the mechanical behaviour of PVC has been analysed. Both Universal Tensile Machines and Impact Testing Machines are used to determine the mechanical properties of CSP/PVC composites (such as the tensile, flexural and impact strength as well as its modulus of elasticity). The experimental results indicated that tensile strength, impact strength and flexural strength improved by 42%, 25% and 23%, respectively, when compared to the pure system.